2021
DOI: 10.1002/pen.25651
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity under shear flow of molten polyethylene filled with carbon nanotubes: Experimental and modeling

Abstract: This work aims to describe the conductivity evolution of polymer composites (polyethylene filled with carbon nanotubes) during a shearing deformation. Rheo‐electric measurements were carried out to observe the shear‐induced fillers network modification. Extended steady shear forces the conductivity to evolve asymptotically to a steady level attesting to an equilibrium between structuring and break up mechanisms in the melted polymer. Numerous experiments were conducted to cover a wide range of shear rate from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Epoxy resin is the most important matrix in fiber reinforced resin matrix composites because of its excellent mechanical and molding process properties. [1][2][3][4][5] The types and applications of epoxy resin are becoming more and more extensive. [6,7] Various types of new high-performance epoxy resin have also produced to satisfy the requirements of national defense, aerospace and other special fields.…”
Section: Introductionmentioning
confidence: 99%
“…Epoxy resin is the most important matrix in fiber reinforced resin matrix composites because of its excellent mechanical and molding process properties. [1][2][3][4][5] The types and applications of epoxy resin are becoming more and more extensive. [6,7] Various types of new high-performance epoxy resin have also produced to satisfy the requirements of national defense, aerospace and other special fields.…”
Section: Introductionmentioning
confidence: 99%
“…Conductive polymer composites (CPCs) are considered organic metals obtained by mixing an insulating polymer matrix (electrical conductivity order of 10 −9 S/cm) with a conductive filler, for example, carbon black (CB), carbon fiber (CF), carbon nanotubes (CNTs), graphene oxide, or graphene. [ 1–8 ] CPCs have high conductivity (~10 −1 S/cm), are light, resistant to oxidation, and, in general, have good mechanical properties compared to the polymer matrix. The electrical conductivity for CPCs using polypropylene (PP), poly(ethylene terephthalate) (PET), and nylon, filled with 20 wt% of CB, has an electrical conductivity of 5.1 × 10 −2 , 9.5 × 10 −2 , and 1.3 × 10 −2 S/cm, respectively, providing a variation up to seven orders of magnitude in comparison with the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the surface conductivity of nanocomposites, it was reported that the melt blending processes may induce a forced alignment effect. 34 This alignment does not result in a well-interconnected network; therefore, surface electrical conductivity is very low even when the percolation threshold is exceeded in the bulk (typically in the range of 10 7 −10 8 Ω/ sq). Surface electrical conductivity can be enhanced by thermal annealing.…”
Section: ■ Introductionmentioning
confidence: 99%